2004
DOI: 10.1302/0301-620x.86b1.14637
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone mineral density in the proximal femur after cementless total hip arthroplasty

Abstract: We investigated prospectively the bone mineral density (BMD) of the proximal femur after implantation of a tapered rectangular cementless stem in 100 patients with a mean age of 60 years (16 to 87). It was determined using dual energy x-ray absorptiometry, performed one week after surgery and then every six months until the end-point of five years. The BMD increased significantly in Gruen zones 2, 4 and 5 by 11%, 3% and 11% respectively, and decreased significantly in Gruen zones 1, 6 and 7 by 3%, 6% and 14% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 33 publications
6
78
2
2
Order By: Relevance
“…Further scans were taken six months and one and two years after index surgery to obtain data from the most active period of bone remodelling [25,26]. Although many factors are known to influence periprosthetic BMD [3], stem design and fixation are the most important [27]. In agreement with previous studies, we observed a strong decrease in BMD for almost all regions.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Further scans were taken six months and one and two years after index surgery to obtain data from the most active period of bone remodelling [25,26]. Although many factors are known to influence periprosthetic BMD [3], stem design and fixation are the most important [27]. In agreement with previous studies, we observed a strong decrease in BMD for almost all regions.…”
Section: Discussionsupporting
confidence: 86%
“…This can be ascribed to blood-flow disruption due to femoral canal preparation three to six months after surgery [28]. The major BMD decreases in the greater trochanter (R1) and the calcar (R7) are typical for straight stems [3,21,23,25,27,[29][30][31][32]. They occur mostly due to stress shielding in the very proximal portion of the calcar due to the vast proximal cross section of the implant [28,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), a higher incidence than that obtained with femoral stems fixed either proximally [19] or distally [1,16] or even with HAcoated implants [4]. In contrast to the findings of Engh et al [6] with AML implants, progressive proximal bone resorption did not stop after the two year follow-up but increased continuously (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…This corresponds with loss of proximal trabecular bone mineral density (BMD) and cortical thickness (Brodner et al 2004;Chandran et al 2012;Stucinskas et al 2012;Jayasuriya et al 2013), distal cortical thickening (Abadie et al 2010), and in cementless implants the formation of trabecular pedestal features (Slack et al 2006). In resurfacing hip replacement (RHR), replacement of the femoral articular cartilage and a layer of supporting bone with a stiff metal shell leads to cancellous bone resorption inside the femoral head and a narrowing of the femoral neck at its junction with the head.…”
Section: Introductionmentioning
confidence: 99%